2019
DOI: 10.1055/s-0039-1677681
|View full text |Cite
|
Sign up to set email alerts
|

Association between Industry Payments and Scholarly Impact among Academic Ophthalmologists

Abstract: Purpose The aim of this article is to examine the association between industry payments to ophthalmologists and scholarly impact. Design Retrospective cross-sectional study. Methods All ophthalmology faculty at United States accredited ophthalmology residency programs were included in this study. The main exposure was industry payments to ophthalmologists in 2016, as reported in the Centers for Medicare and Medicaid Services Open Payments Database. The primary outcome was Hirsch index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Third, FCOIs may influence academia and authors of academic publications as there is an association with increased academic productivity 19,20 and impact 21 . An analysis of 435 authors of haematology and oncology papers in the top 3 general medical (e.g., New England Journal of Medicine ) and oncology journals (e.g., The Lancet Oncology ) found that for every $10,000 in general payments received from the pharmaceutical industry by an author, there was an associated increase of 1.99 more papers published 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, FCOIs may influence academia and authors of academic publications as there is an association with increased academic productivity 19,20 and impact 21 . An analysis of 435 authors of haematology and oncology papers in the top 3 general medical (e.g., New England Journal of Medicine ) and oncology journals (e.g., The Lancet Oncology ) found that for every $10,000 in general payments received from the pharmaceutical industry by an author, there was an associated increase of 1.99 more papers published 22 .…”
Section: Discussionmentioning
confidence: 99%
“…18 Third, FCOIs may influence academia and authors of academic publications as there is an association with increased academic productivity 19,20 and impact. 21 An analysis of 435 authors of haematology and oncology papers in the top 3 general medical (e.g., New England Journal of Medicine) and oncology journals (e.g., The Lancet Oncology)…”
Section: Discussionmentioning
confidence: 99%
“…Given this influence, this study aims to understand what differences, if any, exist for industry payments to ophthalmologists before and after onset of the COVID-19 pandemic. Several prior publications have used the Open Payments Database to address industry payments to ophthalmologists, and we look to specifically analyzed any changes in industry payments to ophthalmologists before and after the beginning of the COVID-19 pandemic made possible by the availability of 2021 data [ 4 , 7 , 14 16 ]. This study additionally serves as an update on general research payment trends to ophthalmologists.…”
Section: Discussionmentioning
confidence: 99%